Simulasi Sistem Keamanan Jaringan Komputer Berbasis IPS Snort dan Honeypot Artilery - Alja Aminanto; Wiwin Sulistyo (AITI, 2019)
The Intrusion Prevention System (IPS) Snort is a server security System that can prevent attacks by examining and recording all data packets as well as recognizing packets with sensors, when the attack has been identified, IPS Snort will deny the access (block) and log of all data packets identified. However by using only IPS Snort which can only check and note the Allert attacks that are incoming in less sense to secure a server by collaborating with the other server's secure system in the sense of being able to make the network security of the server better. Honeypot Artillery chosen which works when there is a Hacker trying to penetrate through open ports can be detected as if hackers can break through the system, then Honeypot Artillery will provide information about who attackers and how the attacker could enter the Snort IPS system for later record in the database that can be viewed on the Web interface, Allert recorded on the experiment that has been done in the database as much as 9453 on TCP protocol as much as 9%, UDP as much as < 1%, and ICMP As much as 91%.